Method for controlling carbon content of cemented carbide macroproduct
By using paraffin vapor for carburizing after dewaxing of large cemented carbide products, and controlling the carburizing temperature and time, the problem of uneven carbon content on the surface and core was solved, thereby improving the stability and safety of the products and simplifying the operation process.
Patent Information
- Application Number
- CN202211166322.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-09-23
AI Technical Summary
During the production of large cemented carbide products, the carbon content on the surface and in the core is uneven. Existing technologies pose safety risks or control instability, leading to product quality problems.
By using paraffin vapor for carburizing after dewaxing, and controlling the carburizing temperature and time, the consistency of carbon content on the surface and in the core is ensured. The process involves hydrogen dewaxing, inert gas replacement, vacuum pre-sintering, and vacuum sintering.
This achieves uniformity of carbon content on the surface and in the core of large cemented carbide products, improves product stability and safety, avoids safety risks and material gradient structures, and enhances the internal stress performance of the products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of cemented carbide preparation, and in particular to a method for controlling the carbon content of large cemented carbide products. Background Technology
[0002] During the production of cemented carbide products, organic substances such as paraffin wax are added to facilitate compression molding. However, because cemented carbide is extremely sensitive to carbon content, the organic substances must be removed in subsequent production processes to ensure product performance. During the removal process, due to the large volume of cemented carbide products and the different removal rates between the core and surface, situations often arise where the surface carbon content is appropriate, but the core remains too high, or vice versa. In some large products, surface decarburization even occurs during production, while the core undergoes carburization.
[0003] Currently, the main methods for controlling the uniformity of carbon content in cemented carbide products are as follows: First, hydrogen is used for dewaxing, which can effectively prevent the decomposition of organic matter and reduce carbon production; second, various carbon replenishment measures are used, such as introducing methane or CO gas in the subsequent sintering stage, or applying a carburized layer to the product surface after dewaxing for sintering carbon replenishment.
[0004] Chinese invention patent CN107937861A discloses a method for carbonizing cemented carbide, which mainly involves introducing methane gas during the later stages of sintering (1350-1380℃) to carbonize the surface. Introducing methane or carbon monoxide gas to carbonize the product surface poses a significant safety risk, as both methane and carbon monoxide are flammable gases. Under negative pressure, air can easily enter, potentially igniting the equipment and causing a production safety accident.
[0005] Chinese invention patent CN107008899A discloses a manufacturing process for a cemented carbide top hammer. The process primarily involves applying a layer of rubber-organic material to the top hammer surface after wax removal and product cooling, followed by carbon replenishment during subsequent sintering. After wax removal, due to the low surface carbon content and higher core carbon content, a carburized layer is applied to the product surface. During subsequent sintering, the carbon from this layer is transferred to the product. However, this method suffers from difficulty in controlling the depth of the carburized layer, resulting in poor stability and a tendency for surface carburization.
[0006] Another method is to differentiate carbon content during the product molding process. For example, during pressing, the core material uses a lower amount of molding agent, while the surface material uses a higher amount of molding agent. Although this method has certain advantages in carbon content control, the material gradient structure is too obvious, the internal stress of the product is large, and the product is prone to quality problems during use, making it unsuitable for actual production. Summary of the Invention
[0007] To address the technical problem of poor carbon uniformity between the surface and core of large cemented carbide products, this invention provides a method for controlling the carbon content of large cemented carbide products. By utilizing the carburizing effect of paraffin vapor on the product surface and controlling the carburizing temperature and time, the consistency of carbon content between the surface and core of the large product can be effectively controlled.
[0008] The objective of this invention is achieved through the following technical solution: This invention provides a method for controlling the carbon content of large cemented carbide products, comprising the following steps: S1. The cemented carbide forming blank is subjected to hydrogen dewaxing, and then replaced with an inert gas. S2. Then, vacuum pre-sintering is carried out. During the vacuum pre-sintering process, paraffin vapor is introduced for carburizing at 540-1000℃ for 60-300 minutes. S3. Finally, vacuum sintering is performed, and after cooling, large cemented carbide products are obtained.
[0009] After normal dewaxing, large cemented carbide products exhibit a lower carbon content on the surface and a higher carbon content in the core, resulting in a significant carbon potential difference between the surface and core. Conventional dewaxing processes, whether using hydrogen or negative pressure, inevitably lead to a higher carbon content in the core compared to the surface during the removal of the forming agent (paraffin wax and other organic substances). This difference becomes more pronounced in larger products. This invention addresses this issue by controlling the carbon penetration into the product surface using paraffin vapor after dewaxing of the cemented carbide forming compact. The temperature and time of paraffin vapor carburizing affect the depth and amount of carburized layer. By controlling these parameters within the limits specified in this invention, the problem of consistent carbon content between the surface and core can be effectively solved. Furthermore, the entire process is more stable, preventing excessive carburizing that could result in a higher carbon content on the surface than in the core, or create a significant material gradient structure that increases internal stress. Therefore, this invention achieves consistent carbon content and microstructure in large cemented carbide products, offering a simple, convenient, practical, and effective solution.
[0010] Preferably, in S1, the weight of the cemented carbide forming blank is ≥8kg.
[0011] Preferably, in S1, the hydrogen wax removal is a phased heating and heat preservation process.
[0012] Preferably, in S1, the flow rate of hydrogen is 50-100 L / min.
[0013] Preferably, in S1, the hydrogen dewaxing process is as follows: First stage: heating from room temperature to 260°C for 200–400 min, then holding at 260°C for 60–300 min; Second stage: heating from 260°C to 380°C for 100–500 min, then holding at 380°C for 60–300 min; Third stage: heating from 380°C to 450°C for 60–300 min, then holding at 450°C for 60–300 min; Fourth stage: heating from 450°C to 540°C for 60–300 min, then holding at 540°C for 60–300 min.
[0014] Preferably, in S1, the temperature at which the inert gas is replaced is 540°C; the inert gas is nitrogen or argon.
[0015] Preferably, in S2, the temperature at which the paraffin vapor is introduced is 60–90°C.
[0016] Preferably, in S2, the process of introducing paraffin vapor for carburizing involves first heating a dewaxing tank with hydrogen to remove the wax, maintaining the temperature of the paraffin vapor produced at 60-90°C, and then introducing the paraffin vapor into a sintering furnace for vacuum pre-sintering.
[0017] Because the dewaxing tank stores paraffin wax from the hydrogen dewaxing process, the paraffin vapor in the dewaxing tank is kept at a constant temperature of 60-90℃. At this temperature, the paraffin wax is in a liquid state, with a small amount of paraffin vapor above it. During the vacuum sintering stage, the dewaxing pipeline valve is opened. Once the valve is open, a small amount of paraffin vapor is drawn into the sintering furnace by the vacuum pump. Since the furnace temperature is already higher than the paraffin decomposition temperature, the paraffin vapor is carbonized at high temperature after entering the furnace, forming active carbon molecules. These molecules combine with the product surface, thereby increasing the carbon content on the product surface. By controlling the dewaxing tank temperature, the wax infiltration temperature, and the time, the amount of paraffin wax entering the furnace and the activity of the carbon molecules after carbonization can be effectively controlled. This allows for control over the amount and depth of carbon entering the product, effectively ensuring consistency between the surface and core carbon content of large products.
[0018] Preferably, in S2, the vacuum pre-sintering is performed by heating from room temperature to 540–1000°C for 100–400 minutes, followed by holding at the temperature and introducing paraffin vapor for carburizing, such that the holding time is not less than the carburizing time.
[0019] Preferably, in step S3, the vacuum sintering temperature is 1400–1450°C, and the holding time is 60–120 min.
[0020] The present invention also provides a large cemented carbide product made using the above-described carbon content control method.
[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) After the wax removal of the cemented carbide forming blank is completed, the carbon content of the product surface is controlled by paraffin vapor. The temperature and time of carburizing with paraffin vapor will affect the depth and amount of carburization of the product carburized layer. By controlling it within the range of the present invention, the problem of carbon content consistency between the product surface and the core can be effectively solved. (2) In actual production, paraffin vapor can be obtained directly from the wax discharge tank. The operation is simple, convenient, practical and effective. Detailed Implementation
[0022] The technical solution of the present invention is illustrated below with specific embodiments, but the scope of protection of the present invention is not limited thereto: General Implementation Examples A method for controlling the carbon content of large cemented carbide products includes the following steps: S1. The cemented carbide forming blanks (large products, single weight ≥8kg, generally between 10-200kg) undergo hydrogen dewaxing. The hydrogen flow rate is 50-100L / min. The first stage involves heating from room temperature to 260℃ for 200-400min, then holding at 260℃ for 60-300min. The second stage involves heating from 260℃ to 380℃ for 100-500min, then holding at 380℃ for 60-300min. The third stage involves heating from 380℃ to 450℃ for 60-300min, then holding at 450℃ for 60-300min. The fourth stage involves heating from 450℃ to 540℃ for 60-300min, then holding at 540℃ for 60-300min. After dewaxing, the blanks are purged with nitrogen or argon at 540℃. S2. Vacuum pre-sintering is then performed in a sintering furnace, with the temperature raised from room temperature to 540–1000°C over a period of 100–400 minutes. Paraffin vapor at 60–90°C is then introduced, with the flow rate controlled at 0.1–20 L / min and the pressure at 0.01–0.2 MPa. Carburization is then carried out at 540–1000°C for 60–300 minutes. The paraffin vapor can be obtained from a dewaxing tank heated by a water bath for hydrogen dewaxing, maintaining the temperature of the dewaxing vapor at 60–90°C. The amount of paraffin in the dewaxing tank is 20–35 kg. Vacuum cooling is then performed. S3. Finally, vacuum sintering is carried out, the temperature is raised to 1400-1450℃ and held for 60-120 minutes, and then cooled in the furnace to obtain the large cemented carbide product.
[0023] Example 1 (Hydrogen Dewaxing) The cemented carbide large product blank (cemented carbide top hammer, weight 100kg) formed by normal batching is placed into a vacuum integrated furnace for hydrogen dewaxing. The hydrogen flow rate is 80L / min. The hydrogen dewaxing process used is shown in Table 1. Table 1 temperature time Room temperature to 260℃ (heating) 300min 260℃ (heat preservation) 180min 260~380℃ (heating) 350min 380℃ (heat preservation) 180min 380~450℃ (heating) 180min 450℃ (heat preservation) 180min 450~540℃ (heating) 180min 540℃ (heat preservation) 180min After the wax removal is completed, the hydrogen in the furnace is replaced with nitrogen at 540℃ to ensure that there are no flammable gases in the subsequent sintering process and to ensure production safety.
[0024] Example 2 (Vacuum Pre-sintering) After hydrogen dewaxing in Example 1, the large cemented carbide blanks were pressed into a vacuum pre-sintering chamber and heated to 540–1000°C for 100–400 minutes. Using the equipment's water bath thermostat, the temperature of the dewaxing tank was maintained at 60–90°C. Once the furnace temperature reached 540–1000°C during vacuum pre-sintering, the dewaxing pipe valve was opened, and paraffin vapor (28 ± 2 kg of paraffin in the dewaxing tank) was introduced. Experimental groups were set up with different dewaxing tank temperatures, carburizing temperatures, and times. After carburizing, the products were vacuum cooled and removed from the furnace. The carbon content difference between the inside and outside of the product was measured (carbon content difference = core carbon content - surface carbon content, with a carbon content difference of 0.01). The carbon content test results for experimental groups 1-10 are shown in Table 2. Table 2 Example 3 (Vacuum Sintering) After vacuum pre-sintering in Example 2, the large cemented carbide products of experimental groups 1-10 were subjected to vacuum sintering, heated to 1400℃ and held for 100 min, and then cooled and removed from the furnace to obtain the final products. The cobalt magnetic properties of the final products were tested (cobalt magnetic difference = core cobalt magnetic field - surface cobalt magnetic field, with the cobalt magnetic difference set at 0.1), and the results are shown in Table 3. Table 3 As shown in Table 2, when the temperature of the dewaxing tank is maintained at 60-90℃ (paraffin melting point is 56℃, using refined paraffin wax No. 52-56), at the same carburizing temperature, the longer the carburizing time, the more obvious the carburizing effect; at the same carburizing time, the higher the carburizing temperature, the more obvious the carburizing effect. However, excessively high temperatures or excessively long times can easily lead to an increase in the overall carbon content. After exceeding 300 minutes, the carbon content in the core of the product will also increase, which will lead to an increase in carbon potential.
[0025] The cobalt magnetic properties of the product can also reflect the difference in carbon content. As shown in Table 3, under the dewaxing tank temperature and carburizing temperature and time conditions specified in this invention, the cobalt magnetic properties on the product surface can be significantly improved. When the temperature and time are properly controlled, the consistency of cobalt magnetic properties between the surface and the core can be achieved. However, in terms of trends, when the carburizing temperature is low, such as 540-600℃, although the surface carbon content increases significantly over time, the increase in cobalt magnetic properties on the product surface is not significant. This indicates that at lower temperatures, the carbon activity is lower, and less carbon is bound to the product, with more carbon existing as free carbon. A significant amount of carbon is lost during the subsequent vacuum sintering process, but despite this loss, the surface still has a significant carbon replenishment effect. However, if the carburizing temperature is below 540℃, the carbon replenishment effect will worsen; conversely, if the carburizing temperature is above 1000℃, the surface cobalt magnetic properties will be higher than the core cobalt magnetic properties, and the carbon replenishment effect will also worsen.
[0026] In summary, by opening the dewaxing pipeline valve during the vacuum pre-sintering stage and adjusting the constant temperature of the dewaxing tank, as well as the carburizing temperature and time, paraffin vapor can achieve high-temperature carbonization in the vacuum pre-sintering furnace to form active carbon molecules. This allows for effective carbon control of the product. Through reasonable parameter control, the consistency of carbon content between the surface and core of large products can be achieved. To date, this invention is the most convenient, practical, and effective invention for controlling the internal and external carbon content and microstructure consistency of large cemented carbide products.
[0027] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made using the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A method for controlling the carbon content of large cemented carbide products, characterized in that, Includes the following steps: S1. The cemented carbide forming blank is subjected to hydrogen dewaxing, and then replaced with an inert gas. S2. Vacuum pre-sintering is then performed, which involves heating from room temperature to 540-1000℃ for 100-400 minutes, then holding at that temperature while introducing paraffin vapor for carburizing, ensuring that the holding time is not less than the carburizing time; during the vacuum pre-sintering process, paraffin vapor at 60-90℃ is introduced for carburizing, and carburizing is performed at 540-1000℃ for 60-300 minutes. S3. Finally, vacuum sintering is performed, and after cooling, large cemented carbide products are obtained.
2. The method for controlling the carbon content of large cemented carbide products as described in claim 1, characterized in that, In S1, the weight of the cemented carbide forming blank is ≥8kg.
3. The method for controlling the carbon content of large cemented carbide products as described in claim 1, characterized in that, In S1, the hydrogen wax removal is a phased heating and heat preservation process.
4. The method for controlling the carbon content of large cemented carbide products as described in claim 1, characterized in that, In S1, the flow rate of hydrogen is 50~100L / min.
5. The method for controlling the carbon content of large cemented carbide products as described in any one of claims 1, 3, and 4, characterized in that, In S1, the hydrogen dewaxing process is as follows: the first stage involves heating from room temperature to 260°C for 200-400 minutes, followed by holding at 260°C for 60-300 minutes; the second stage involves heating from 260°C to 380°C for 100-500 minutes, followed by holding at 380°C for 60-300 minutes; the third stage involves heating from 380°C to 450°C for 60-300 minutes, followed by holding at 450°C for 60-300 minutes; and the fourth stage involves heating from 450°C to 540°C for 60-300 minutes, followed by holding at 540°C for 60-300 minutes.
6. The method for controlling the carbon content of large cemented carbide products as described in claim 1, characterized in that, In S2, the process of introducing paraffin vapor for carburizing involves first heating a dewaxing tank with hydrogen to remove the wax, maintaining the temperature of the paraffin vapor produced at 60-90°C, and then introducing the paraffin vapor into a sintering furnace for vacuum pre-sintering.
7. The method for controlling the carbon content of large cemented carbide products as described in claim 1, characterized in that, In S3, the vacuum sintering temperature is 1400~1450℃, and the holding time is 60~120min.
8. A cemented carbide large product manufactured using the carbon content control method as described in any one of claims 1-7.
Citation Information
Patent Citations
Manufacturing technique for hard alloy anvil
CN107008899A
Cemented carbide carbon complementary method
CN107937861A
Carbon content correction preparation method of WC-Co hard alloy
CN106756171A
Production process of hard alloy
CN109055845A
